2022
DOI: 10.3389/fcimb.2022.841138
|View full text |Cite
|
Sign up to set email alerts
|

Use of Bulk Segregant Analysis for Determining the Genetic Basis of Azole Resistance in the Opportunistic Pathogen Aspergillus fumigatus

Abstract: A sexual cycle was described in 2009 for the opportunistic fungal pathogen Aspergillus fumigatus, opening up for the first time the possibility of using techniques reliant on sexual crossing for genetic analysis. The present study was undertaken to evaluate whether the technique ‘bulk segregant analysis’ (BSA), which involves detection of differences between pools of progeny varying in a particular trait, could be applied in conjunction with next-generation sequencing to investigate the underlying basis of mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 72 publications
2
7
0
Order By: Relevance
“…Genotyping confirmed that the most common aerosolized resistanceassociated polymorphisms were TR 34 /L98H (59%) and TR 46 / Y121F/T289A (6%). We further found that 30% of TEB-resistant isolates did not contain any polymorphisms in the cyp51A promoter or coding regions suggesting that the existence of alternative resistance mechanisms as has previously been noted (table S1) (23). This is of concern in the clinical setting as only the two former mutations are picked up by commercially available polymerase chain reaction (PCR) diagnostic methods, although previously unidentified mutations leading to resistance will be identified by phenotypic testing of minimum inhibitory concentration (MIC) providing that there is an isolate available to test.…”
Section: Resultssupporting
confidence: 75%
“…Genotyping confirmed that the most common aerosolized resistanceassociated polymorphisms were TR 34 /L98H (59%) and TR 46 / Y121F/T289A (6%). We further found that 30% of TEB-resistant isolates did not contain any polymorphisms in the cyp51A promoter or coding regions suggesting that the existence of alternative resistance mechanisms as has previously been noted (table S1) (23). This is of concern in the clinical setting as only the two former mutations are picked up by commercially available polymerase chain reaction (PCR) diagnostic methods, although previously unidentified mutations leading to resistance will be identified by phenotypic testing of minimum inhibitory concentration (MIC) providing that there is an isolate available to test.…”
Section: Resultssupporting
confidence: 75%
“…Genotyping confirmed that the most common aerosolized resistance-associated polymorphisms were TR 34 /L98H (59%) and TR 46 /Y121F/T289A (6%). We further found that 30% of TEB-resistant isolates did not contain any polymorphisms in the cyp51A promoter or coding regions suggesting the existence of alternative resistance mechanisms as have previously been noted ( 22 ) ( Table S1 ). This is of concern in the clinical setting as only the two former mutations are picked up by commercially available PCR diagnostic methods, although previously unidentified mutations leading to resistance will be picked up by phenotypic testing of minimum inhibitory concentration (MIC) providing that there is an isolate available to test.…”
Section: Manuscriptsupporting
confidence: 72%
“…Finally, it was confirmed that flower bulb waste material could serve as a natural substrate for sex by the demonstration that such material could be utilized successfully to perform sexual crosses in the laboratory. Ashton et al, (2022) also demonstrate that the sexual cycle can be used for genetic analysis. They used the 'bulk segregant analysis (BSA)' technique together with next-generation sequencing and a newly developed bioinformatic pipeline to investigate the underlying basis of monogenic traits in A. fumigatus.…”
mentioning
confidence: 85%